Principle of National Treatment in Applying Trademark Registration in Indonesia - Elsa Savira; Runtung; Agus Sardjono; Jelly Leviza (Journal of Finance and Business Digital, 2023)
One of the basic principles adopted in the TRIPs Agreement is the principle of  national treatment, In general,  this principle of national treatment  states that foreigners will get the same treatment as the treatment given by a country for its own citizens. This research uses normative juridical research methods with a descriptive type of research. Meanwhile, data analysis is used normative legal research (legal research). Principle National Treatment in International Law Rules Related to Trademarks National Treatment set on Trademark Law Treaty and Paris Convention Application of Principles National Treatment Trademark Registration in Indonesia has not been regulated in the current trademark legislation other than dispute resolution by considering and using the principle of National Treatment Also still sidelined in law enforcement related to trademark disputes.